GLOBAL TRENDS IN ADOLESCENT DEVELOPMENT AND THEIR IMPACT ON ISLAMIC EDUCATION SYSTEMS: A PSYCHOEDUCATIONAL REVIEW AND PROGRESSIVE ISLAMIC VALUES PERSPECTIVE - Imtihanatul Ma'isyatuts Tsalitsah -; Muhammad Wahid Nur Tualeka; Carlos Lazaro Prawirosastro (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
The acceleration of globalization and advancements in digital technology have brought significant changes to the lives of adolescents worldwide. Today’s youth grow up in a social context that is no longer confined to their local environment but is shaped by cross-cultural interactions, global information flows, and digital social dynamics. These shifts directly affect how adolescents think, learn, interact, and develop their identities. This article aims to identify key global trends in adolescent development and analyze their implications for education systems, while emphasizing the importance of integrating Islam berkemajuan (progressive Islamic values) as a moral and spiritual foundation to address global challenges. The study employs a systematic literature review of scientific publications, international organizational reports, and global education policies published between 2015 and 2025. The findings highlight five major global trends influencing adolescent development: digitalization and social media, cross-cultural openness, environmental awareness and social activism, increasing mental health issues, and changes in learning patterns and global identity formation. These trends have significant implications for education systems, including the need for adaptive curricula, enhanced digital literacy, transformation of educators’ roles, and the strengthening of character education. The integration of progressive Islamic values, as reflected in Qur’an Surah Al-Qashash [QS. Al-Qashash: 77], serves as a crucial strategy to maintain balance between global advancement and the development of noble character. This article recommends strengthening collaboration between educators, policymakers, and communities to respond to global challenges through holistic, contextual, and spiritually grounded education.